Carbonation of concrete with construction and demolition waste based recycled aggregates and cement with recycled content. (20th February 2020) - Sáez del Bosque, I.F.; Van den Heede, P.; De Belie, N.; Sánchez de Rojas, M.I.; Medina, C.
Highlights: The mean carbonation depth in recycled concretes is 1.07–1.20 times greater than conventional concretes. The CO2 penetration coefficient is below the mm/year 0.5 "good quality concrete". The minimum design cover could be reduced in member manufactured with the new concretes. The inclusion of MRA and OPC-CW does not compromise reinforcement passivity. Abstract: Durability is a major concern in concrete (particularly recycled concrete) structures exposed to carbonation-induced corrosion, given the social, economic, environmental and safety implications involved. This article explores carbonation performance in concrete with 25% or 50% mixed recycled construction and demolition waste aggregate, alone or in conjunction with cement containing 25% fired clay construction and demolition waste. Irrespective of cement type, the mean carbonation depth was slightly greater in materials with 25% or 50% recycled aggregate than in concretes with 100% natural aggregate, although the difference was not statistically significant for the 25% replacement ratio. In all the concretes studied, the carbonation coefficient was below the 4 mm/yr 0.5 indicative of good quality. Based on the prediction model proposed in Spain's concrete code, reinforcement passivity was guaranteed in all these types of concrete when exposed to class XC1 to XC4 carbonation environments for substantially longer than their 100 year design service life.